Post-Pandemic Epidemiology of Respiratory Infections among Pediatric Inpatients in a Tertiary Hospital in Shanghai, China - Siyuan Lan; Changjuan Gu; Shuanglong Lu; Ning Zhou; Xiaohong Qiao (MDPI AG, 2024)
Background: After the removal of the three-year epidemic control restrictions, Chinese children were confronted with heightened risks of respiratory infections. We aimed to investigate the post-pandemic (2023) epidemiology of respiratory infections among pediatric inpatients in a tertiary hospital in Shanghai, China, and compare it with the pre-pandemic (2019) levels. Methods: A total of 2644 pediatric inpatients were enrolled based on discharge time and divided into group 2019 (n = 1442) and group 2023 (n = 1202). Information on the demographic characteristics, diagnoses, and pathogen test results (Mycoplasma pneumoniae, MP; Chlamydia pneumoniae, CP; Legionella pneumophila, LP; Influenza A, IFA; Influenza B, IFB; Parainfluenza virus, PIV; respiratory syncytial virus, RSV; Coxsackie virus, COX; Adenovirus, ADV; Epstein-Barr virus, EBV) was collected and analyzed. Results: Significant increases were found in the overall test positivity rates (64.6% vs. 46.7%), mixed infection rates (17.4% vs. 9%), and proportion of severe cases (25.5% vs. 3.7%) after the pandemic than those before it. Compared with 2019, the incidences of MP, IFA, LP, RSV, and ADV remarkably increased, while those of IFB and COX decreased, with no obvious differences noted for CP, PIV, and EBV in 2023. A significantly higher MP-positive detection rate was noticed in children aged 1-6 years in 2023 than in 2019. The incidence of RSV infection began to rise in August 2023, earlier than the conventional epidemic season. Conclusions: Compared with the pre-pandemic levels, the overall test positivity rates of atypical pathogens and viruses among pediatric inpatients significantly increased, and alterations in the disease spectrum, epidemic season, and age of prevalence were observed after the COVID-19 pandemic.